Effectiveness of Opportunities Provided to Youth in Surkhandaryo Region in 2016-2022 (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This research study analyzed the opportunities provided to young people in Surkhandarya region in 2016-2022 and the effectiveness of their results. The opportunities provided to young people, including reforms in areas such as education, vocational training, employment, and social assistance, and their impact on the development of the region were studied. The study analyzed the role of young people in society, the conditions created for them, and how these opportunities affected their personal and social development. It also considered recommendations for increasing the effectiveness of the opportunities provided to young people, future development strategies, and ways to improve regional governance.